PARTISIPASI MASYARAKAT TERHADAP PELESTARIAN HUTAN MANGROVE DI KELURAHAN KABONGA BESAR KECAMATAN BANAWA KABUPATEN DONGGALA PROVINSI SULAWESI TENGAH - Aghniyah, Nurul; Umar, Syukur; Hamka, Hamka (Universitas Tadulako, 2020)
Mangrove Forests in Central Sulawesi, one of which is in Kabonga Besar Subdistrict, Kacamatan Banawa, Donggala Regency, is a mangrove forest ecosystem that can be utilized by the surrounding community to meet their daily needs and economy. The mangrove forest must be protected its sustainability, because it has many functions and benefits for humans, and deserves to be considered as a support for the surrounding community. This research implemented for 3 months, from October to December 2019. The research method use in this research is based on the data sources which are primer data and secondary data. There are 4 types of data collection technique use in this research, they are observation, interview, questionnaire and documentation. Results from the direct observation in field shows that Kabonga Besar's society has a big roll of participation to keep the Mangrove Forest sustainability, and comprehend the functions and benefits of mangrove forest for their lives. Judging from the attitude of community participation in replanting with a percentage of scoring 59.5% strongly participated and 40.5% participated. The attitude of the community in the conversion of the function of mangroves into fishponds with a percentage of scoring 66.7% did not participate and 33.3% did not participate. Mangrove has a lot of benefits, there are : as prevention of abrasion, residence for marine biota, bird residence, hurricane preventer, to help protect the coral reefs and also to protect from natural disaster (e.g tsunami)Keywords: Hutan Mangrove, Pelestarian, Partisipasi Masyarakat